Differences in psychological skills in table tennis players depending on sport level - Gonzalez-Garcia, H.; Pelegrin, A. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The objective of the study was to find out if there are differences in the psychological abilities related to sport performance, according to the level of sport practice (professional vs amateurs, international successes vs no international successes) in table tennis players. The sample consisted of 133 table tennis players from around Spain. In order to measure the psychological abilities of table tennis athletes, the Spanish version of the "Psychological Characteristics Related to Sport Performance Questionnaire" (CPRD) was used. The results did not show significant differences (p>.05) in mental abilities, which include: stress control, influence of performance evaluation, motivation, mental ability and team cohesion, among professional and amateur table tennis players. On the other hand, no significant differences (p>.05) were found in these mental abilities among athletes with and without international success. It was concluded that there are no differences in psychological skills depending on sport practice level of Spanish table tennis players.